Opportunity Identification and Creation as Factors of Firm Internationalisation - Agnieszka Żur (Entrepreneurial Business and Economics Review)
Objective: This paper aims to establish if, why and how, in given institutional and industry contexts, the identification and/or creation and exploitation of opportunity may result in a higher intensity of internationalisation processes in firms.